A competence‐based and multidimensional operationalization and measurement of employability - Heijde, Claudia M. Van Der; Van Der Heijden, Beatrice I. J. M. (Human Resource Management, 2006)
AbstractEmployability is a critical requirement for enabling both sustained competitive advantage at the firm level and career success at the individual level. We propose a competence‐based approach to employability derived from an expansion of the resource‐based view of the firm. In this contribution, we present a reliable and valid instrument for measuring employability. This measure is based on a five‐dimensional conceptualization of employability, in which occupational expertise is complemented with generic competences. Two sources of raters (employees and their immediate supervisors) are involved in developing and testing the measure. Since the five dimensions of employability explain a significant amount of variance in both objective and subjective career success, the predictive validity of the tool is promising. This instrument facilitates further scientific HRM research and is of practical value in light of job and career assessments, recruitment, staffing, career mobility, and development practices. © 2006 Wiley Periodicals, Inc.